Peningkatan Hasil Belajar Soal Cerita Luas Trapesium Layang-layang Menggunakan Strategi Polya Kelas V SD - arlita, ofni; masniladevi, masniladevi; harni, harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
ABSTRACTThis study was based on the low learning outcomes of students. The purpose of this study was to improve the learning outcomes about trapezoidal and kite story by using the polya strategy in grade V SDN 34 Tanah Sirah Kecamatan Lubuk Begalung, Padang.  The subjects in this study were teachers and 30 students. The result of observation of lesson plan in cycle I was 73.2, and the result in second cycle was increasing which was 92.9. Implementation of learning aspects of teacher in cycle I was 79.2 and it increased in cycle II which was 94.4. Implementation of learning aspects of students in cycle I was 79.2, and in cycle II it increased to 91.7. The improvement of student learning outcomes can be seen from the three aspects, the result in learning outcomes also showed improvement from cycle I to cycle II which were 76.9 in cycle I and 83.8 in cycle II.Key word. learning outcomes, polya strategy Keywords : The Improvement Of Student Learning Outcomes, The Polya Strategi